2018
DOI: 10.1002/cbdv.201800437
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the C‐Terminal Tail Dynamics: Structural and Molecular Perspectives into the Therapeutic Activities of Novel CRMP‐2 Inhibitors, Naringenin and Naringenin‐7‐O‐glucuronide, in the Treatment of Alzheimer's Disease

Abstract: The collapsin response mediator protein (CRMP‐2) is hyperphosphorylated in Alzheimer's disease (AD). These phosphorylation events are mediated by specific kinase proteins, GSK3β and Cdk5, and occur at target phosphorylation sites majorly located at the C‐terminal tail of CRMP‐2. The abilities of naringenin (NAR) and naringenin‐7‐O‐glucuronide (NAR‐7‐O‐G) to selectively bind CRMP‐2 and reduce its phosphorylation have been previously demonstrated; the molecular interplay between these events remains unresolved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Before the binding of naringenin and naringenin-7- O -glucuronide to the C-terminal tail, these residues have more flexibility, activity, and are more susceptible to phosphorylation. But these effects reversed after binding of naringenin and naringenin-7- O -glucuronide [59]. On this regard, another molecular docking study demonstrated that the occupation of CRMP2 by naringenin restricts the access of the phosphorylated enzyme to the terminal H19 helix especially in Tyr479 residue which is the susceptible residue for phosphorylation [60].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Before the binding of naringenin and naringenin-7- O -glucuronide to the C-terminal tail, these residues have more flexibility, activity, and are more susceptible to phosphorylation. But these effects reversed after binding of naringenin and naringenin-7- O -glucuronide [59]. On this regard, another molecular docking study demonstrated that the occupation of CRMP2 by naringenin restricts the access of the phosphorylated enzyme to the terminal H19 helix especially in Tyr479 residue which is the susceptible residue for phosphorylation [60].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Genome-wide studies, genetic linkage analyses, proteomic analyses, and translational approaches have revealed altered expression levels of CRMPs in neurodevelopmental disorders, such as schizophrenia, attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD) [3,4,5,6,7,8]. Similar findings have been observed for neurological disorders such as Alzheimer’s disease [9,10,11] and hyperalgesia syndrome [12,13,14,15]. Furthermore, during the past decade, many studies using knockout (KO) mice have demonstrated the role of CRMPs in the pathogenesis of neurodevelopmental disorders, as described in Section 3 below.…”
Section: Introductionmentioning
confidence: 78%
“…Several small molecules that have been shown to bind CRMP2 are lacosamide (Wilson et al, 2012(Wilson et al, , 2014, lanthionine ketimine (LK; Hensley et al, 2010aHensley et al, , 2013Hensley and Harris-White, 2015), edonerpic maleate (Abe et al, 2018) and naringenin (Ghofrani et al, 2015;Lawal et al, 2018). These molecules are considered candidates for application in the treatment of some of the CRMP2-related pathological conditions discussed above.…”
Section: Crmp2-interacting Drugsmentioning
confidence: 99%
“…Naringenin has demonstrated the ability to bind and decrease CRMP2 phosphorylation (Yang et al, 2016;Lawal et al, 2018). This action of changing CRMP2's phosphorylated status and hence the binding of cytoskeletal elements may account for the ability of naringenin to improve AD pathology and cognitive deficits in mouse models of AD.…”
Section: Crmp2-interacting Drugsmentioning
confidence: 99%